ANALISIS SISTEM REMUNERASI PEGAWAI TRANS METRO DALAM PELAYANAN ANGKUTAN PUBLIK DI KOTA PEKANBARU - Raden Imam Al Hafis (UIR Press, 2014)
This study aims to determine the extent to which the management of Trans Metro Pekanabaru do Remuneration System (payroll) in Trans Metro Pekanbaru and the factors that cause delays in payment of salaries, then refers to the study of literature that made indiktor research that essentially is expected to provide a clear picture the system of remuneration Trans Metro Pekanbaru. In this study the data and information collected using a questionnaire and the data information is used as a basis to explain the variables of the study This study is survey descriptive, which aims to explain in a systematic, factual and accurate information on the facts and the relationship between the phenomena encountered in system Trans Metro employee remuneration in Pekanbaru. The study population was Head of Lent, Managing Director of Trans Metro, Head of Human Resources & General and the Chief Financial Officer and Driver, Kernet and Pejaga stop. While the sample set is Head of Lent, Managing Director of Trans Metro, Head of Human Resources & General and Chief Financial Officer (Key Informant) and 10 Drivers, 10 Kernet and 35 Guard stops. Sampling technique using purposive sampling method. This type of data is primary data obtained through questionnaires and interviews and secondary data in the form of profiles Trans Metro Pekanbaru, MOU, Pekanbaru Mayor's decision, as well as other relevant data, obtained in place of the study. As for the results of research conducted by researchers with the title